Reinforcing Elderly Management in Brunei Darussalam: an Islamic Approach to Aging - Firdaus, Muhammad Furqan; Kurniawan, Cecep Soleh (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2024)
Despite the existence of regulations and policies for the elderly in Brunei Darussalam, the creation of guidelines and frameworks for the management of the elderly based on Islamic views in Brunei Darussalam is still not available. Thus, this study examines (i) Islamic and western views on the aging phase and the age of the elderly, (ii) The constraints faced by the elderly when leading the aging phase, (iii) Mechanisms of effort and dynamism of the government of Brunei Darussalam in preserving the welfare of elderly Brunei Darussalam and (iv) Develop a comprehensive framework for the management of the elderly in Brunei Darussalam based on Islamic guidance. This study is based on qualitative methods through a library approach, document analysis, interviews, and observations. The data analysis is carried out using a descriptive method through the programming software NVivo Version 14. The results of the study prove that the management of the elderly through Islamic perspectives can deal with the issues of aging in Brunei Darussalam and minimize the risk of aging.